The Economy, Sustainable Development, and Energy International Conference 2019
DOI: 10.3390/proceedings2221595
|View full text |Cite
|
Sign up to set email alerts
|

LCA Analysis of Three Types of Interior Partition Walls Used in Buildings

Abstract: Numerous studies have been done with the purpose of identify and try to reduce the impact generated by the construction industry, mainly focused on the use stage in the search to increase the energy efficiency. However, as these stage has been improved and the impact produced has been reduced, it has become evident the need to focus the research on the elements and life cycle stages that follow on the affectation scale. Therefore, the present research analyzes the importance of the embodied energy and the affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Andere Veröffentlichungen fokussieren sich lediglich auf die Herstellungsphase (Module A1-A5). [10,11,5] Da die Vorgaben nach DIN 15804 für Bauwerksanalysen konzipiert sind, fanden im Rahmen dieser Untersuchung Anpassungen für eine bauteilorientierte Lebenszykluskostenbetrachtung der in Abschnitt 1 genannten Phasen statt. Die Nutzungsphase wird lediglich qualitativ bewertet.…”
Section: Grundlagen Und Methodisches Vorgehenunclassified
“…Andere Veröffentlichungen fokussieren sich lediglich auf die Herstellungsphase (Module A1-A5). [10,11,5] Da die Vorgaben nach DIN 15804 für Bauwerksanalysen konzipiert sind, fanden im Rahmen dieser Untersuchung Anpassungen für eine bauteilorientierte Lebenszykluskostenbetrachtung der in Abschnitt 1 genannten Phasen statt. Die Nutzungsphase wird lediglich qualitativ bewertet.…”
Section: Grundlagen Und Methodisches Vorgehenunclassified
“…The study also investigated whether employing AAC in building construction is economically feasible and whether it might affect energy use and greenhouse gas emissions. The LCA of three types of interior partition walls used in buildings-gypsum plasterboard, AAC blocks, and calcium silicate blocks-has been given by Valencia-Barba et al [17] and Ferrández-García et al [18]. The findings indicated that gypsum plasterboard has the most significant environmental impact, whereas AAC blocks have the lowest, especially regarding energy consumption and ability to cause global warming.…”
Section: Literature Reviewmentioning
confidence: 99%